Comparison of electromagnetic and piezoelectric vibration energy harvesters with different interface circuits. (May 2016) - Wang, Xu; Liang, Xingyu; Hao, Zhiyong; Du, Haiping; Zhang, Nong; Qian, Ma
Abstract: A frequency response analysis has been conducted for a single degree of freedom vibration energy harvester connected to four different interface circuits. The performance and characteristics of both electromagnetic and piezoelectric harvesters have been analysed and compared. The main research outcome is the disclosure of similarity and duality of the electromagnetic and piezoelectric harvesters with different interface circuits. The contribution of this paper is to provide a new method to identify a vibration energy harvester with the best interface circuit and the most stable performance. Highlights: Disclose similarity and duality of the electromagnetic and piezoelectric harvesters with different interface circuits. Compare the sensitivity of the harvesting performance to the uncertainty of electric resistance for the electromagnetic and piezoelectric harvesters with different interface circuits. Develop a new method to identify a vibration energy harvester with the best interface circuit and the most stable performance.